359. INTRATUMORAL MICROBIOME IMPACTS IMMUNE INFILTRATES IN TUMOR MICROENVIRONMENT AND PREDICTS PROGNOSIS IN ESOPHAGEAL SQUAMOUS CELL CARCINOMA PATIENTS. (24th September 2022) - Xie, Xuan; Xie, Xuan; Zhang, Shuishen; Ma, Xiaofan; Zhan, Jing; Pan, Chuqing; Zhang, Huizhong; Xie, Xiuying; Wen, Jing
Abstract: Emerging evidence suggests different intratumoral microbiome exists in different tumors and plays a crucial function in carcinogenesis. However, whether intratumoral microbiome in esophageal squamous cell carcinoma (ESCC) impacts clinical outcomes and its mechanism remains unclear. 16S rDNA amplicon sequencing was performed on surgical resected samples from 106 ESCC patients including 25 paired tumorous and non-tumorous tissues (NTs) to analyze intratumoral microbiome abundance and its composition. Multiplex fluorescent immunohistochemistry (mfIHC) staining was used to profile the phenotypes of immune infiltrates in tumor microenvironment (TME). Both Shannon index and operational taxonomic units (OTUs), representing alpha-diversity of microbiome, were found significantly lower in tumors comparing to the corresponding NTs. Multivariate analysis revealed that the intratumoral Shannon index, the relative abundance of Lactobacillus and the pTNM stage were independently associated with patients' overall survival. Furthermore, the relative abundance of Lactobacillus and Shannon index were both positively correlated with the proportions of PD-L1+ epithelial cells (ECs) and tumor-associated macrophages (TAMs, and Shannon index was negatively correlated with the proportions of natural killer cells (NKs) and activated cytotoxic T cells (aCTLs) in TME, indicating an immunosuppressive microenvironment. These findings underscored for the first time that the high abundance of intratumoral Lactobacillus and microbiome alpha-diversity were associated with poor long-term survival of ESCC patients, which might be achieved by increasing PD-L1 + ECs and PD-L1 + TAMs and decreasing aCTLs and NKs in TME.